Diagnóstico da energia elétrica na extração de rochas ornamentais no estado do Espírito Santo - de Souza Santos, Yolacir Carlos; Gome de Jesus, Renata; Antônio Vasconcelos, João (Latin American Journal of Energy Research, 2022)
This study aimed to prepare a diagnostic of the use of electricity in the extractive sector of dimensional stones in Espírito Santo, using as a tool the analysis of information from the Annual Mining Reports (RAL’s) presented to the National Mining Agency (ANM), as well as the application of questionnaires aimed at companies in the extractive sector in Espírito Santo. The information obtained through the RAL’s provided an understanding of the main sources of electrical energy of the energy intensity indicator referring to the production of dimensional stones. The analysis of the data presented through the questionnaires provided the opportunity for a more refined understanding of the main sources of electric energy, as well as the perception of companies regarding electric energy management, energy efficiency actions and knowledge about the ISO 50.001 standard. Finally, it was found that the mineral extraction sector presents itself with a great opportunity in terms of energy management and energy efficiency. Keywords: Dimensional stones; energetic diagnostic; energy management; energy efficiency.